Complement Component 3 is Necessary to Preserve Myocardium and Myocardial Function in Chronic Myocardial Infarction. (September 2014) - Wysoczynski, Marcin; Solanki, Mitesh; Borkowska, Sylwia; van Hoose, Patrick; Brittian, Kenneth R.; Prabhu, Sumanth D.; Ratajczak, Mariusz Z.; Rokosh, Gregg
Abstract Activation of the complement cascade (CC) with myocardial infarction (MI) acutely initiates immune cell infiltration, membrane attack complex formation on injured myocytes, and exacerbates myocardial injury. Recent studies implicate the CC in mobilization of stem/progenitor cells and tissue regeneration. Its role in chronic MI is unknown. Here, we consider complement component C3, in the chronic response to MI. C3 knockout (KO) mice were studied after permanent coronary artery ligation. C3 deficiency exacerbated myocardial dysfunction 28 days after MI compared to WT with further impaired systolic function and LV dilation despite similar infarct size 24 hours post‐MI. Morphometric analysis 28 days post‐MI showed C3 KO mice had more scar tissue with less viable myocardium within the infarct zone which correlated with decreased c‐kitpos cardiac stem/progenitor cells (CPSC), decreased proliferating Ki67pos CSPCs and decreased formation of new BrdUpos/α‐sarcomeric actinpos myocytes, and increased apoptosis compared to WT. Decreased CSPCs and increased apoptosis were evident 7 days post‐MI in C3 KO hearts. The inflammatory response with MI was attenuated in the C3 KO and was accompanied by attenuated hematopoietic, pluripotent, and cardiac stem/progenitor cell mobilization into the peripheral blood 72 hours post‐MI. These results are the first to demonstrate that CC, through C3, contributes to myocardial preservation and regeneration in response to chronic MI. Responses in the C3 KO infer that C3 activation in response to MI expands the resident CSPC population, increases new myocyte formation, increases and preserves myocardium, inflammatory response, and bone marrow stem/progenitor cell mobilization to preserve myocardial function. Stem Cells2014;32:2502–2515